Zitkala-S̈a : letters, speeches, and unpublished writings, 1898-1929 - Zitkala-S̈a, 1876-1938 (International studies in sociology and social anthropology, 2018)
"Zitkala-Sa: Letters, Speeches, and Unpublished Writings, 1898-1929, edited by Tadeusz Lewandowski, offers a fascinating, intimate portrait of the Yankton Sioux writer and activist Gertrude Simmons Bonnin (1876-1938). Gertrude Bonnin, better known by her Lakota name, Zitkala-Sa, was one of the most prominent American Indians of the early 20th century. A talented writer, orator, and musician, she devoted much of her life to the protection of Native peoples. As such, Bonnin corresponded with many other distinguished persons within the early Native rights movement, including Carlos Montezuma, Richard Henry Pratt, and Arthur C. Parker, as well as Fathers Martin Kenel and William H. Ketcham of the Bureau of Catholic Indian Missions. This volume gathers together Bonnin's letters, lesser-known writings and speeches, illuminating her private and public struggles."--Provided by publisher.